PELUANG DAN TANTANGAN EKOWISATA GUNA MENDORONG PERTUMBUHAN BISNIS DAN EKONOMI DI BANYUWANGI - Salsabila, Enggita; Wulandari, Gusti Ayu; Riski, Gusti Ayu Agustina (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2024)
Ecotourism has become a rapidly growing trend in the tourism industry, offering nature-based tourism experiences while also contributing to environmental conservation and empowering local communities. This research aims to identify opportunities and challenges for ecotourism development in Banyuwangi to drive business and economic growth, analyze its economic impacts, and formulate strategies to optimize the benefits of ecotourism sustainably. Through a systematic review of various empirical studies, this research reveals ecotourism opportunities in creating employment, attracting tourists with specific interests, and promoting conservation of local natural and cultural heritage. However, challenges faced include negative environmental impacts, cultural shifts within communities, and inadequate infrastructure. Recommended strategies include the application of sustainable principles, increased community involvement, infrastructure investment, technology utilization, multi-stakeholder partnerships, monitoring and evaluation, optimization model development, as well as increased awareness and education. This research provides valuable insights for stakeholders in optimizing the ecotourism potential in Banyuwangi to drive sustainable economic growth.